The Cold Forming Analysis of Eccentric Parts - Yang, Chih-Cheng; Sumampow, Yoel; Cruz, Sunshine Nazareno Dela (European Journal of Applied Sciences, 2023)
In this study, a multi-stage cold forming process for the manufacture of eccentric parts is studied numerically with low carbon steel AISI 1022. The forming processes through five stages and four stages include two-step forward extrusion, eccentric upsetting, and backward extrusion over a moving punch. The numerical simulations of cold forming are conducted using the code of DEFORM-3D. The formability of the workpiece is studied numerically, such as the effect on forging load responses, maximum forging loads, effective stress and effective strain distributions and metal flow pattern. The maximum effective stress of 819 MPa at the third stage is the largest among the stages. The maximum effective stresses of the last stages for the four-stage forming and five-stage forming are almost the same. The effective strain distributions of the last stages for the four-stage forming and five-stage forming are very similar. The flow line distributions of the last stages both for the four-stage forming and five-stage forming are also very similar. For the maximum axial forging force and forming energy, the third stage of eccentric upsetting at the upper end is the largest among the stages. The total maximum axial forging loads from the first to the last stages are 795.8kN for the five-stage forming and 590.4kN for the four-stage forming; and the total forming energies are about 0.751kJ for the five-stage forming and 0.671kJ for the four-stage forming. Although the total maximum axial forging loads and total forming energy of the four-stage forming are smaller than those of the five-stage forming, the maximum lateral forging force in the last stage of the four-stage forming is almost five times that of the last stage of the five-stage forming. Increasing lateral forging force may lead to wear and damage of the punch. Moreover, the inner surfaces of the hexagonal cavity at the upper end are relatively uneven because of simultaneous eccentric upsetting and backward extrusion in the last stage of the four-stage forming.